Spin-lattice effects in selected antiferromagnetic materials (Review Article) - Zherlitsyn, S.; Yasin, S.; Wosnitza, J.; Zvyagin, A.A.; Andreev, A.V.; Tsurkan, V. (Физика низких температур, 2014)
Spin-lattice effects play an important role in many magnetic materials. In this short review, we give some examples of such effects studied in low-dimensional, frustrated as well as uranium-based antiferromagnets. Utilizing ultrasound measurements at low temperatures and high magnetic fields provides valuable information on the spin-strain interactions. Specifically phase transformations and critical phenomena in magnetic systems with
strong spin-lattice interactions are fruitful grounds for sound-velocity and sound-attenuation measurements.